Factors associated with utilization of adolescent-friendly services in Bhaktapur district, Nepal - Krishtee Napit; Khadga Bahadur Shrestha; Sudip Ale Magar; Rashmi Paudel; Barsha Thapa; Bhup Raj Dhakal; Archana Amatya (BMC, 2020)
Abstract Background The status of adolescent sexual and reproductive health (SRH) in Nepal is alarming. Adolescent-friendly services (AFS) were introduced to cater the health needs of adolescents. Optimal utilization of the services with wider accessibility is required to prevent adolescents from adopting life-threatening behaviors that result in poor SRH-related outcomes. Despite the upgrading of health facilities to adolescent-friendly sites, studies reveal low utilization of the service. However, these studies failed to explore the factors influencing the low levels of service utilization in these adolescent-friendly facilities. This study quantified the utilization of AFS and identified factors associated with its utilization among adolescents of Bhaktapur district. Methods A cross-sectional survey of 362 systematic randomly selected adolescents from four village development committees of Bhaktapur district was conducted, using a self-administered questionnaire. Relationships between utilization of AFS and associated factors were determined by multivariate logistic regression at a level of significance with a p value of less than 0.05 and adjusted odds ratio. Key informant interviews and focus group discussions with adolescents were used to collect qualitative data which were then described using thematic analysis. Result About a quarter (24.7%) of the respondents had utilized the adolescent-friendly services. Factors positively associated with the utilization of services included adolescents aged 15-19 years, female, heard about AFS, lack of fear of being seen while getting SRH services, lack of shyness about receiving SRH services, and the perceived need for SRH services as soon as illness became apparent. The qualitative findings revealed lack of awareness about the services, socio-cultural barriers, confidentiality, feasible service hours, and the preference for of same-sex service providers as the factors affecting utilization. Conclusion The utilization of adolescent-friendly services was very low in Bhaktapur district. Most of the adolescents were unaware of the existence of the AFS which emphasizes the need to focus on the increasing awareness of SRH and AFS by the government in coordination with local schools, clubs, etc. Creating an enabling environment in the service delivery sites, and ensuring privacy and confidentiality, as well as ensuring same-sex service providers and feasible service hours to adolescents, could increase the service utilization.